Intrathymic growing bronchogenic cyst mimicking thymoma: A case report - Grigoroiu, Madalina; Paisley, Sarah; Brian, Emmanuel; Natali, Delphine (Frontiers in Oncology, 2023)
Intra-thymic bronchogenic cysts are extremely rare lesions and the differential diagnosis with a banal thymic cyst or a solid tumor can be problematic. Thymic carcinomas arising within thymic cysts have also been reported. We report a case of radical thymectomy for a slowly growing small thymic cyst. The pathological finding revealed a bronchogenic cyst rather than thymic neoplasm.